Cytokinocytes: the diverse contribution of keratinocytes to immune responses in skin - Jiang, Yanyun; Tsoi, Lam C.; Billi, Allison C.; Ward, Nicole L.; Harms, Paul W.; Zeng, Chang; Maverakis, Emanual; Kahlenberg, J. Michelle; Gudjonsson, Johann E. (JCI insight, 2020)
The skin serves as the primary interface between our body and the external environment and acts as a barrier against entry of physical agents, chemicals, and microbes. Keratinocytes make up the main cellular constitute of the outermost layer of the skin, contributing to the formation of the epidermis, and they are crucial for maintaining the integrity of this barrier. Beyond serving as a physical barrier component, keratinocytes actively participate in maintaining tissue homeostasis, shaping, amplifying, and regulating immune responses in skin. Keratinocytes act as sentinels, continuously monitoring changes in the environment, and, through microbial sensing, stretch, or other physical stimuli, can initiate a broad range of inflammatory responses via secretion of various cytokines, chemokines, and growth factors. This diverse function of keratinocytes contributes to the highly variable clinical manifestation of skin immune responses. In this Review, we highlight the highly diverse functions of epidermal keratinocytes and their contribution to various immune-mediated skin diseases.